Cytoskeleton regulators CAPZA2 and INF2 associate with CFTR to control its plasma membrane levels under EPAC1 activation - Santos, JD; Pinto, FR; Ferreira, JF; Amaral, MD; Zaccolo, M; Farinha, CM (Portland Press, 2020)
Cystic Fibrosis (CF), the most common lethal autosomic recessive disorder among Caucasians, is caused by mutations in the gene encoding the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) protein, a cAMP-regulated chloride channel expressed at the apical surface of epithelial cells. Cyclic AMP regulates both CFTR channel gating through a protein kinase A (PKA)-dependent process and plasma membane (PM) stability through activation of the exchange protein directly activated by cAMP1 (EPAC1). This cAMP effector, when activated promotes the NHERF1:CFTR interaction leading to an increase in CFTR at the PM by decreasing its endocytosis. Here, we used protein interaction profiling and bioinformatic analysis to identify proteins that interact with CFTR under EPAC1 activation as possible regulators of this CFTR PM anchoring. We identified an enrichment in cytoskeleton related proteins among which we characterized CAPZA2 and INF2 as regulators of CFTR trafficking to the PM. We found that CAPZA2 promotes wt-CFTR trafficking under EPAC1 activation at the PM whereas reduction of INF2 levels leads to a similar trafficking promotion effect. These results suggest that CAPZA2 is a positive regulator and INF2 a negative one for the increase of CFTR at the PM after an increase of cAMP and concomitant EPAC1 activation. Identifying the specific interactions involving CFTR and elicited by EPAC1 activation provides novel insights into late CFTR trafficking, insertion and/or stabilization at the PM and highlighs new potential therapeutic targets to tackle CF disease.